A nationwide analysis on the interaction between frailty and beta-blocker therapy in hip fracture patients - Maximilian Peter Forssten; Ahmad Mohammad Ismail; Ioannis Ioannidis; Per Wretenberg; Tomas Borg; Yang Cao; Marcelo Augusto Fontenelle Ribeiro; Shahin Mohseni (2023)
Hip fracture patients, who are often frail, continue to be a challenge for healthcare systems with a high postoperative mortality rate. While beta-blocker therapy (BBt) has shown a strong association with reduced postoperative mortality, its effect in frail patients has yet to be determined. This study's aim is to investigate how frailty, measured using the Orthopedic Hip Frailty Score (OFS), modifies the effect of preadmission beta-blocker therapy on mortality in hip fracture patients.This retrospective register-based study included all adult patients in Sweden who suffered a traumatic hip fracture and subsequently underwent surgery between 2008 and 2017. Treatment effect was evaluated using the absolute risk reduction (ARR) in 30-day postoperative mortality when comparing patients with (BBt+) and without (BBt-) ongoing BBt. Inverse probability of treatment weighting (IPTW) was used to reduce potential confounding when examining the treatment effect. Patients were stratified based on their OFS (0, 1, 2, 3, 4 and 5) and the treatment effect was also assessed within each stratum.A total of 127,305 patients were included, of whom 39% had BBt. When IPTW was performed, there were no residual differences in observed baseline characteristics between the BBt+ and BBt- groups, across all strata. This analysis found that there was a stepwise increase in the ARRs for each additional point on the OFS. Non-frail BBt+ patients (OFS 0) exhibited an ARR of 2.2% [95% confidence interval (CI) 2.0-2.4%, p < 0.001], while the most frail BBt+ patients (OFS 5) had an ARR of 24% [95% CI 18-30%, p < 0.001], compared to BBt- patients within the same stratum.Beta-blocker therapy is associated with a reduced risk of 30-day postoperative mortality in frail hip fracture patients, with a greater effect being observed with higher Orthopedic Hip Frailty Scores.